LncRNA RHPN1‐AS1 inhibition induces autophagy and apoptosis in prostate cancer cells via the miR‐7‐5p/EGFR/PI3K/AKT/mTOR signaling pathway. Issue 12 (20th September 2022) - Ma, Xiulong; Ren, Hongtao; Zhang, Yang; Wang, Baofeng; Ma, Hongbing
Abstract: LncRNA RHPN1‐AS1 (RHPN1‐AS1) has been confirmed to promote tumor progression in multiple cancers and is upregulated in prostate cancer (PCa), but whether it has an effect on PCa progression remains unclear. In this study, we found that PCa patients with high RHPN1‐AS1 expression had a shorter survival time, and RHPN1‐AS1 was significantly upregulated in PCa tissues and cells. Based on informatics analysis we predicted that miR‐7‐5p binds to 3′UTR of RHPN1‐AS1 and epidermal growth factor receptor (EGFR) and verified it by luciferase reporter gene assay. Subsequently, we transfected PCa cells with RHPN1‐AS1 overexpression vector (RHPN1‐AS1), knockdown plasmids (sh‐RHPN1‐AS1) and/or miR‐7‐5p mimics or inhibitor and/or overexpression vector (EGFR) or small interfering RNA of EGFR (si‐EGFR) or its control, and found that overexpression of RHPN1‐AS1 inhibited miR‐7‐5p expression and promoted EGFR expression, silencing RHPN1‐AS1 inhibited proliferation and invasion, and induced G2/M arrest, apoptosis and autophagy in PCa cells. 3MA (an inhibitor of autophagy)‐mediated autophagy inhibition attenuated RHPN1‐AS1 inhibition‐induced apoptosis. Overexpression miR‐7‐5p or silencing EGFR promoted LC3‐I to LC3‐II conversion, enhanced autophagy activity, induced cleaved‐caspase‐3 expression and apoptosis in PCa cells. Furthermore, overexpression of RHPN1‐AS1 promoted phosphorylation of phosphatidylinositol 3‐kinase (PI3K), AKT and mTOR, inhibited LC3‐I to LC3‐II conversion and reduced apoptosis in PCa cells, while GSK2126458 (an inhibitor of PI3K) reversed the effect of RHPN1‐AS1 on PCa cells. In summary, RHPN1‐AS1 acted as a ceRNA of miR‐7‐5p to upregulate EGFR expression, silencing RHPN1‐AS1 suppressed PCa tumor progression by inducing autophagy and apoptosis in PCa cells through the miR‐7‐5p/EGFR/PI3K/AKT/mTOR pathway.